2007
DOI: 10.1007/s00383-006-1872-8
|View full text |Cite
|
Sign up to set email alerts
|

Erdosteine treatment attenuates oxidative stress and fibrosis in experimental biliary obstruction

Abstract: Oxidative stress, in particular lipid peroxidation, induces collagen synthesis and causes fibrosis. The aim of this study was to assess the antioxidant and antifibrotic effects of erdosteine on liver fibrosis induced by biliary obstruction in rats. Liver fibrosis was induced in Wistar albino rats by bile duct ligation (BDL). Erdosteine (10 mg/kg, orally) or saline was administered for 28 days. Serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) and lactate dehydrogenase (LDH) levels were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
8
1
1
Order By: Relevance
“…oxygen free radicals have a role in the pathogenesis of tissue injury in obstructive jaundice (Peres et al 2000;Padillo et al 2002;Sener et al 2006Sener et al , 2007. Free radical ablation for the treatment of cholestatic liver injury has been shown to have beneficial effects in the prevention of fibrosis and oxidative damage following biliary obstruction.…”
mentioning
confidence: 99%
“…oxygen free radicals have a role in the pathogenesis of tissue injury in obstructive jaundice (Peres et al 2000;Padillo et al 2002;Sener et al 2006Sener et al , 2007. Free radical ablation for the treatment of cholestatic liver injury has been shown to have beneficial effects in the prevention of fibrosis and oxidative damage following biliary obstruction.…”
mentioning
confidence: 99%
“…The final result is a protective effect on tissues that reduces lipid peroxidation, neutrophil infiltration and cell apoptosis mediated by noxious agents 3,28 . The hepatoprotective effect of erdosteine has also been presented in many studies [5][6][7][8][9][10][11] . Saritas et al 5 investigated the efficacy of erdosteine usage in acetaminophen-induced liver damage and compared it with N-acetyl cysteine (NAC) in the treatment and prevention of liver toxicity due to acetaminophen overdose.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Moreover, erdosteine has been shown to be effective for protecting the liver fibrosis and oxidative injury due to biliary obstruction. Sener et al 8 reported that serum AST, ALT, LDH, and plasma cytokines were elevated in the bile duct ligated (BDL) group and were significantly decreased by erdosteine treatment. It was also shown that erdosteine administration alleviated the BDL-induced oxidative injury of the liver and improved the hepatic functions, and it was suggested that these effects were associated with the antioxidant and antifibrotic properties of erdosteine.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that increased concentration of bile acids induce lipid peroxides, probably related to the stimulation of phagocytic activity in the polymorphonuclear leukocytes and inflammatory cells, which are present after biliary tract obstruction and enhance the tissue injury (2,3). Several clinical and experimental studies have shown that oxygen free radicals have a role in the pathogenesis of tissue injury in obstructive jaundice (4)(5)(6)(7). Thus free radical ablation for the treatment of cholestatic liver injury has been shown to have beneficial effects in the prevention of fibrosis and oxidative damage following biliary obstruction.…”
Section: Introductionmentioning
confidence: 99%